Minimasi Kecacatan pada Produk Dripper 1 dengan Metode TRIZ dan Analytic Network Process pada CV Pudak Scientific - Silvia Apriandani; Didit Damur Rochman (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
A product defect is defined as a problem related to the quality of the product. The company will endeavor to minimize the occurrence of defective products in order to enhance its overall productivity. The total production of Dripper 1 in the period between May 2023 and May 2024 amounted to 4,227 units, with a defect rate of 22.7%. The proportion of defective products has exceeded the permitted tolerance limit of 5%, necessitating the implementation of quality control measures through the introduction of improvements to the production process. The most appropriate method for improvement is the TRIZ method, as it is designed to facilitate the generation of creative solutions. However, the solutions provided are merely alternative solutions; thus, the ANP method is necessary to determine which alternative is the most optimal. The production of Dripper 1 is characterized by eight distinct types of defects, namely black dot defects, flow marks, scratches, silver marks, burn marks, discoloration, bubbles, and brass flakes. Among these eight types of defects, black dot defects, flow marks, and scratches are the most prevalent, with respective frequencies of 449, 237, and 114 units. The alternatives resulting from the TRIZ method include the installation of filters, periodic machine cleaning, the design of auxiliary tools, modifications to gate sizes, periodic inspections, the creation of standard operating procedures (SOPs), and operator training. According to the ANP method, the alternative with the highest weight is the installation of filters, with a value of 0.29177 (29.177%), and is therefore selected as the solution to the problem.